NON-NATIVE ENGLISH TEACHERS’ STRATEGIES ON TEACHING CULTURE IN AN EFL YOUNG LEARNERS’ CLASSROOM - Marsha, Putri Nydia; M.A., Ph.D., Prof. Dra. Yetti Zainil (Universitas Negeri Padang, 2025)
The present study identified the NNESTs’ strategies to integrate culture in their teaching of the target language. This research was conducted by using descriptive research design which are observation classroom and interview for support observation data. The data source from this research is five NNESTs, who teach Story Kids Level in ELSI Padang. From the findings of observation classroom, it reveals that only five of these strategies were consistently implemented by all teachers at ELSI Padang. These strategies included teachers explicitly presents cultural information, uses authentic materials to teach culture, and encourages students to discuss a document or event from another culture then relate it to one’s own. Furthermore, the teacher also facilitates discussions on students personal and critical opinions about the topic related to culture and encourages students to explain or describe their feelings and attitudes about the text, the characters, and the events. In addition, from the total of sixteen identified strategies, four were not implemented by any of the five teachers during their culture teaching at ELSI Padang. The data indicates that these unimplemented strategies include asking students to identify and explain cultural references found in the learning materials and encouraging students to identify areas of misunderstanding in intercultural interactions in their learning materials. Additionally, the teachers did not implement strategies such as guiding students to analyze cultural stereotypes and leads discussions on differences in cultural values and beliefs across cultures.